The value of shapley as a strategy for Resource Optimization on Power Line Communication (PLC) (2015)
This article proposes the use of cooperative game theory, supported by the use of bankruptcy game of the and the Shapley value, as a strategy to optimize the allocation of resources in each node, according to service demand, the number of stations and the conditions of the PLC channel -- The paper proposes a scenario under saturated traffic conditions, in order to assess the degree of optimization that the value of Shapley can perform in front of traffic and channel conditions clearly established -- It is concluded that the use of cooperative game theory, supported on the Shapley value, can be considered as an excellent alternative when making resource optimization processes in a PLC channel y with the possibility to be implemented in economic embedded systems, because it does not require complex operations for its estimation